2006
DOI: 10.1002/jcc.20481
|View full text |Cite
|
Sign up to set email alerts
|

Coupled atomic charge selectivity for optimal ligand‐charge distributions at protein binding sites

Abstract: Charge optimization as a tool for both analyzing and enhancing binding electrostatics has become an attractive approach over the past few years. An interesting feature of this method for molecular design is that it provides not only the optimal charge magnitudes, but also the selectivity of a particular atomic center for its optimal charge. The current approach to compute the charge selectivity at a given atomic center of a ligand in a particular binding process is based on the binding-energy cost incurred upo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…This concept was recently extended to predict a coupled charge selectivity (CSq), which is defined as the energetic cost of changing an atomic charge by one electron charge from its optimal value while allowing all other charges in the molecule to reoptimize. 69 The CSq method was applied to inhibitors of COX-2 such as celecoxib, which have nanomolar affinity for carbonic anhydrase II (CAII). The CSq analysis identified that the ionized sulfonamide group of celecoxib was well optimized to bind CAII and was highly charge selective whereas there was little charge selectivity of this group binding to COX2.…”
Section: Structure-based Selectivity Design Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This concept was recently extended to predict a coupled charge selectivity (CSq), which is defined as the energetic cost of changing an atomic charge by one electron charge from its optimal value while allowing all other charges in the molecule to reoptimize. 69 The CSq method was applied to inhibitors of COX-2 such as celecoxib, which have nanomolar affinity for carbonic anhydrase II (CAII). The CSq analysis identified that the ionized sulfonamide group of celecoxib was well optimized to bind CAII and was highly charge selective whereas there was little charge selectivity of this group binding to COX2.…”
Section: Structure-based Selectivity Design Considerationsmentioning
confidence: 99%
“…Experimentally, the binding affinity of P1-Met BPTI is 7.4 kcal/mol worse than P1-Lys BPTI, indicating the strong selectivity for a positively charged group in this site, in agreement with the charge optimization predictions. This concept was recently extended to predict a coupled charge selectivity (CSq), which is defined as the energetic cost of changing an atomic charge by one electron charge from its optimal value while allowing all other charges in the molecule to reoptimize . The CSq method was applied to inhibitors of COX-2 such as celecoxib, which have nanomolar affinity for carbonic anhydrase II (CAII).…”
Section: Structure-based Selectivity Design Considerationsmentioning
confidence: 99%
“…They explained octanol-water partition coeicients of organic compounds with the atomic charges [16,21]. Bhat et al [22] reported optimal ligand-charge distribution at protein-binding sites with the help of atomic charge Highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) are very popular quantum chemical descriptors. The strongest Frontier orbitals (FO)…”
Section: Quantitative Structure Activity Relationshipmentioning
confidence: 99%
“…3,4 Nonspherical geometries and alternative basis sets for ligand charge distributions were then addressed, 5,6 and the method was extended to exact molecular shapes. 712 A framework for optimizing electrostatic specificity has also been developed. 13,14 Calculation of the electrostatic potentials is generally done by solving the linearized Poisson–Boltzmann (LPB) equation, but other forms of linear response theory are applicable.…”
Section: Introductionmentioning
confidence: 99%
“…22 Other applications include E. coli glutaminyl-tRNA synthetase binding to its cognate substrates, 23 protein inhibitors of HIV-1 cell entry, 24 the interface between protein kinases and their ligands, 25 small-molecule influenza neuraminidase inhibitors, 26 and the celecoxib ligand binding independently to COX2 and CAII. 12 Recently, charge optimization and protein design together identified tighter binding peptides to HIV-1 protease that were studied experimentally. 27 Binding specificity optimization probed ligand binding in the model system of HIV protease, other proteases, and their inhibitors.…”
Section: Introductionmentioning
confidence: 99%